2012
DOI: 10.1159/000339674
|View full text |Cite
|
Sign up to set email alerts
|

Being Pregnant and Diagnosed with Breast Cancer

Abstract: Breast cancer during pregnancy (BCP) is an important subgroup within the young and very young breast cancer patients. It accounts for about 1% of all breast cancers. Due to an increased awareness, the attitude towards breast cancer during pregnancy has changed and, today, women with BCP are more likely to receive standard chemotherapy and have a term delivery instead of being advised to interrupt the pregnancy or undergo an early preterm delivery. This increased knowledge is based on small cohort studies and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…2 It is generally reported that it accounts for about one third of all pregnancy-related cancers. We confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is generally reported that it accounts for about one third of all pregnancy-related cancers. We confirm this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other types of breast cancers, a prognosis of this subtype is poorer due to fewer therapeutic options being available 11. Generally, younger women diagnosed with breast cancer tend to have this more aggressive form of cancer compared with older women, with over 90% of under the 40s being diagnosed with an invasive ductal carcinoma, mostly undifferentiated and most without receptor expression 12…”
Section: Discussionmentioning
confidence: 99%
“…These include postponing chemotherapy until the second and third trimester, avoiding radiotherapy and hormonal therapy until post partum and ensuring chemotherapy is stopped a month before delivery. Furthermore, the literature recommends that delivery of the baby should be as close to term as possible, with worse fetal prognoses recorded in early preterm deliveries 12. These proposals aim to optimise the outcomes of both the mother and the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Bildgebende Verfahren zum Staging des Mammakarzinoms während der Schwangerschaft sind dann indiziert, wenn sie nachfolgende therapeutische Strategien beeinflussen. Wird das Risiko für Metastasen als gering eingeschätzt, besteht grundsätzlich auch die Möglichkeit, Staginguntersuchungen erst nach der Entbindung durchzuführen und somit den Fetus keinen unnötigen Strahlenrisiken auszusetzen [4,22].…”
Section: Stagingunclassified